Finland : Financial Sector Assessment Program: Technical Note-Banking Supervision. (IMF Staff Country Reports; Country Report, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program (FSAP) for Finland in the area of banking supervision. The regulatory and supervisory framework for liquidity and funding risk has improved since the last FSAP, but certain vulnerabilities persist and require greater attention. Finnish banks continue to rely extensively on wholesale funding, as noted in the 2010 FSAP. Although supervisory action has managed to mitigate the problem, many banks remain heavily exposed to the risk of a dry-up of unsecured wholesale funding. Also, banks hold covered bonds issued by other banks as part of their liquidity buffer.